Exploring the Service Quality determinants of Solar Product Dealers. (March 2019) - Kumar, Vikas; Hundal, Bikramjit Singh; Kaur, Komalpreet
The present study explored the determinants affecting service quality of solar product dealers. The study is based on primary data, collected from a total of 345 solar pump users from different villages and rural areas of Punjab. Exploratory factor analysis, confirmatory factor analysis, and paired sample t-test have been used to examine the data. Furthermore, the SERVQUAL scale has been used to measure the service quality of solar product dealers. Paired sample t-test was used to measure the users' expectation and perception gap between service quality dimensions. The results validated that five factors namely reliability, responsiveness, assurance, empathy, and tangibility influence service quality of solar product dealers and there is no significant difference between perceptions and expectations of solar product users except for the responsiveness dimension. As far as gap analysis is concerned, the dimension 'responsiveness' was responsible for the highest gap score. So, perceptions of solar product users are not fully being met with their expectations.